Harmonisasi Antar Umat Beragama Dalam Mewujudkan Kerukunan Di Desa Karya Mulya Kota Prabumulih - Balegha, Hujjatul; Alyyah, Arum Kholifatul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This article analyzes the role of social capital in realizing harmony between religious communities in Karya Mulya Village, Rambang Kapak Tengah, Prabumulih City, which has diversity in the lives of its people. Departing from the reality of a pluralistic society that is prone to conflict. However, it is different from Karya Mulya Village. The existence of diversity between religious communities has made Karya Mulya Village a harmony conscious village because the people are aware of differences and have a high attitude of tolerance between religious communities. Using Putnam's concept of social capital as an analytical tool to determine success in inter-religious harmony in Karya Mulya Village, Prabumulih City. This research uses qualitative research with field research to find out directly the harmony that exists in Karya Mulya Village. The results of the research show that the social capital in achieving harmony in Karya Mulya Village is that tolerance is an agreed norm within the community considering that Karya Mulya is a village with high religious diversity. There is coordination and communication between communities which can foster mutual trust between fellow community members. Trust has positive implications in social life. The various successes achieved through cooperation in realizing inter-religious harmony in the previous time in this network will encourage the continuation of cooperation in the future in Karya Mulya Village.